2019
DOI: 10.4018/978-1-5225-9257-0.ch008
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Second-Generation Cryptocurrency Valuation Metrics

Abstract: This chapter builds on the body of work that has depicted cryptocurrency as a model for science and higher education funding. To that end, this work examines the degree to which one or more cryptocurrencies would need to be adopted and achieve a network effect prior to implementation of such a funding model. Empirical data from three different cryptocurrencies were examined. The current work deploys generalized autoregressive conditional heteroskedasticity (GARCH) to analyze stochastic volatility. This work co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this regard, we want to remark that Shanaev et al (2019) recently showed that some of the previously reported positive relationships between crypto-coins prices and their hashrate, or between crypto-coins prices and their transaction counts, were either spurious due to serial correlation or inconsistent due to endogeneity. Therefore, the development of "second-generation valuation metrics" for cryptocurrencies (Lehner et al 2019;Shanaev et al 2019) able to accommodate both modern empirical finance asset-pricing models and theory-driven valuation models is definitively a compelling avenue for further research. be equal to 21 million bitcoin.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we want to remark that Shanaev et al (2019) recently showed that some of the previously reported positive relationships between crypto-coins prices and their hashrate, or between crypto-coins prices and their transaction counts, were either spurious due to serial correlation or inconsistent due to endogeneity. Therefore, the development of "second-generation valuation metrics" for cryptocurrencies (Lehner et al 2019;Shanaev et al 2019) able to accommodate both modern empirical finance asset-pricing models and theory-driven valuation models is definitively a compelling avenue for further research. be equal to 21 million bitcoin.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we want to remark that Shanaev et al (2019) recently showed that some of the previously reported positive relationships between crypto-coins prices and their hashrate, or between crypto-coins prices and their transaction counts were either spurious due to serial correlation or inconsistent due to endogeneity. Therefore, the development of "second-generation valuation metrics" for cryptocurrencies (Lehner et al (2019) and Shanaev et al (2019)) able to accommodate both modern empirical finance asset-pricing models and theory-driven valuation models is definitively a compelling avenue for further research.…”
Section: Discussionmentioning
confidence: 99%